The approach–avoidance dilemma at the heart of group‐based support: Evidence that group identification increases willingness to seek support at the same time that identity‐based support threat reduces it. (15th May 2018) - Butler, Tamara L.; McKimmie, Blake M.; Haslam, S. Alexander
Abstract: Despite the benefits of shared group membership, group members often experience an approach–avoidance dilemma when seeking support. At the same time that group members' willingness to seek support is increased by the positive implications of group identification (the approach hypothesis ), it is reduced by negative implications, including the capacity for support to threaten their standing in the group (the avoidance hypothesis ). As this dilemma predicts, we find evidence that as participants' group identification increases, their willingness to seek support increases, but that this willingness is simultaneously reduced by increased identity‐based support threat (Study 1, N = 125; Study 2, N = 161). Furthermore, manipulated support threat decreases willingness to seek support. In a team‐based game (Study 3, N = 117), support threat is reduced when group norms encourage support‐seeking, leading to increases in support‐seeking behavior through increases in willingness to seek support, as predicted by the avoidance‐reduction hypothesis . Implications for strategies to promote effective social support in intragroup contexts are discussed.